Student readiness factors for online distance learning among Malaysian public universities during COVID-19: a conceptual model / Nor Aslily Sarkam ... [et al.] - Sarkam, Nor Aslily; Nasrudin, Nur Hasni; Mohamad Razi, Nor Faezah; Ahmad Junid, Rosida (Universiti Teknologi MARA, 2022)
Students’ academic performance will be positively affected by their readiness to learn. This study investigated the association between university students' learning readiness variables and academic achievement. Therefore, the purpose of this study is to identify student readiness factors that influence students' academic performance and to propose a conceptual model that will improve students’ academic performance in the ODL system. A set of self-administered questionnaires were distributed to 233 students attending public higher education institutions using a quantitative research approach. Using the Structural Equation Modelling (SEM) technique, the student's readiness was determined by investigating the cause-and-effect relationship between three readiness factors: (i) Efforts Expectancy (EE), (ii) Attitudes (ATT), and (iii) Facilitating Conditions (FC), towards the Performance Expectancy (PE) factor. The results suggested that Facilitating Conditions (FC) is the most influential readiness component and has a significant impact on students' learning acceptance, which directly increases their learning achievement. With great optimism, it is hoped that this study will aid MOHE and university decision-makers in gaining an understanding of the critical factors that drive the online distance learning (ODL) system. Implementing the proposed conceptual model will thereby simplify the acceptance of the system.